Question
upstudy study bank question image url

5. \( \int_{-1}^{0} 2 x \cdot e^{-x} d x \) есептеңіз.

Ask by Stewart Stephens. in Kazakhstan
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Результат интеграла равен -2.

Solution

Calculate the integral \( \int_{-1}^{0} 2x*e^(-x) \, dx \). Evaluate the integral by following steps: - step0: Evaluate using partial integration formula: \(\int_{-1}^{0} 2xe^{-x} dx\) - step1: Evaluate the integral: \(\int 2xe^{-x} dx\) - step2: Use properties of integrals: \(2\times \int xe^{-x} dx\) - step3: Prepare for integration by parts: \(\begin{align}&u=x\\&dv=e^{-x}dx\end{align}\) - step4: Calculate the derivative: \(\begin{align}&du=dx\\&dv=e^{-x}dx\end{align}\) - step5: Evaluate the integral: \(\begin{align}&du=dx\\&v=-e^{-x}\end{align}\) - step6: Substitute the values into formula: \(2\left(x\left(-e^{-x}\right)-\int 1\times \left(-e^{-x}\right) dx\right)\) - step7: Calculate: \(2\left(-xe^{-x}-\int -e^{-x} dx\right)\) - step8: Calculate: \(-2xe^{-x}-2\times \int -e^{-x} dx\) - step9: Evaluate the integral: \(-2xe^{-x}-2e^{-x}\) - step10: Return the limits: \(\left(-2xe^{-x}-2e^{-x}\right)\bigg |_{-1}^{0}\) - step11: Calculate the value: \(-2\) Результат интеграла \( \int_{-1}^{0} 2x \cdot e^{-x} dx \) равен -2.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

Есепті шешу үшін интегралды табу керек: \[ I = \int_{-1}^{0} 2 x \cdot e^{-x} \, dx \] Уақыт sparen, интегралды IBP (интегралды интеграциялау) әдісімен шеше аламыз. IBP формуласы: \[ \int u \, dv = uv - \int v \, du \] Мұндағы, \( u = 2x \) және \( dv = e^{-x} dx \). Осыдан, \( du = 2 \, dx \) және \( v = -e^{-x} \). Жазамыз: \[ I = \left[ -2x e^{-x} \right]_{-1}^{0} - \int_{-1}^{0} -2 e^{-x} \, dx \] Алдымен шекаралардағы мәндерді есептейік: \[ \left[ -2x e^{-x} \right]_{-1}^{0} = (-2(0)e^{0}) - (-2(-1)e^{1}) = 0 + 2e = 2e \] Енді интегралды есептейік: \[ \int_{-1}^{0} -2 e^{-x} \, dx = -2 \left[ -e^{-x} \right]_{-1}^{0} = -2 \left( -e^{0} + e^{1} \right) = -2(-1 + e) = 2(1 - e) \] Бірінші бөлім 2e, екінші бөлім 2(1 - e). Сол жағдайда: \[ I = 2e + 2(1 - e) = 2e + 2 - 2e = 2 \] Сондықтан интеграл шешімі: \[ \int_{-1}^{0} 2 x \cdot e^{-x} \, dx = 2 \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy